The convergence of industrial property rights - Ion E. Anghel; Victor Iancu (Romanian Academy, National Institute for Economic Research, 2010)
As regards the performance required for the development of the knowledge-based society, we view industrial property as an important level in this context. Therefore, in this paper we present (on a comparative basis) the system of industrial property rights and their protection in the European Union, the United States of America and Romania. At the same time, we analyse aspects of institutional, legislative and functional convergence/divergence of industrial property rights. The approach to these aspects is made on a correlative basis and deals with the interdependence of the industrial property field and the RDI field.
Keywords: O34; P48; K29; O57; 330; institutional convergence; competitiveness; invention patent; industrial design; innovation; trademark; industrial model.